Stress engineering on the electronic and spintronic properties for a GaSe/HfSe2 van der Waals heterostructure. (14th February 2019) - Ke, Congming; Tang, Weiqing; Zhou, Jiangpeng; Wu, Zhiming; Li, Xu; Zhang, Chunmiao; Wu, Yaping; Yang, Weihuang; Kang, Junyong
Abstract: In this work, the electronic and spintronic properties of GaSe/HfSe2 heterostructure under different strains are investigated through first-principles calculations. The results indicate that GaSe/HfSe2 heterostructure has an intrinsic type I band alignment, and the band structure is sensitive to the strain. A transition from type-I to type-II band alignment is found under a tensile stress. The evolution of the band structures is analyzed by the decomposed-projected band structures. Moreover, switchable spin textures of GaSe/HfSe2 heterostructure with different strains are also predicted. The controllable electronic spintronic properties of GaSe/HfSe2 heterostructure hold a great promise in applications of nanoelectronics and spintronics.